Effects of the sodium‐glucose co‐transporter‐2 inhibitor dapagliflozin on estimated plasma volume in patients with type 2 diabetes. Issue 12 (17th September 2019) - Dekkers, Claire C. J.; Sjöström, C. David; Greasley, Peter J.; Cain, Valerie; Boulton, David W.; Heerspink, Hiddo J. L.
Abstract: Aims: To compare the effects of the sodium‐glucose co‐transporter‐2 (SGLT2) inhibitor dapagliflozin on estimated (ePV) and measured plasma volume (mPV) and to characterize the effects of dapagliflozin on ePV in a broad population of patients with type 2 diabetes. Materials and methods: The Strauss formula was used to calculate changes in ePV. Change in plasma volume measured with 125 I‐human serum albumin (mPV) was compared with change in ePV in 10 patients with type 2 diabetes randomized to dapagliflozin 10 mg/d or placebo. Subsequently, changes in ePV were measured in a pooled database of 13 phase 2b/3 placebo‐controlled clinical trials involving 4533 patients with type 2 diabetes who were randomized to dapagliflozin 10 mg daily or matched placebo. Results: The median change in ePV was similar to the median change in mPV (−9.4% and −9.0%) during dapagliflozin treatment. In the pooled analysis of clinical trials, dapagliflozin decreased ePV by 9.6% (95% confidence interval 9.0 to 10.2) compared to placebo after 24 weeks. This effect was consistent in various patient subgroups, including subgroups with or without diuretic use or established cardiovascular disease. Conclusions: ePV may be used as a proxy to assess changes in plasma volume during dapagliflozin treatment. Dapagliflozin consistently decreased ePV compared to placebo in a broad population of patients with type 2 diabetes.